2015
DOI: 10.1186/s40352-015-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between childhood abuse, anger and violent behavior among a sample of sex offenders

Abstract: BackgroundIncreasing attention has focused on the emotional dysregulation that can result from adverse childhood experiences among those who commit sexually violent crimes. While studies confirm a relationship between child maltreatment and anger the research is limited and it is unclear how anger and child maltreatment effect the use of violence during the commission of the sex crime.MethodsThis study examined the relationship between childhood maltreatment, anger and violent behavior by reviewing the records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…42 Interestingly, the offenders reported experiencing high anger and hostility, both of which are cognitive and affective subtraits of the multidimensional concept of aggression measured on AQ. 43 The pattern has been confirmed in previous study where anger and hostility were commonly reported as one of the few problematic psychosocial features common to sexual offenders, pedophilic offenders, exhibitionists, and offenders with multiple paraphilias. 44 In fact, hostility often becomes the key parameter that differentiates the group of sexual offenders from nonsexual offenders.…”
Section: Original Articlesupporting
confidence: 75%
“…42 Interestingly, the offenders reported experiencing high anger and hostility, both of which are cognitive and affective subtraits of the multidimensional concept of aggression measured on AQ. 43 The pattern has been confirmed in previous study where anger and hostility were commonly reported as one of the few problematic psychosocial features common to sexual offenders, pedophilic offenders, exhibitionists, and offenders with multiple paraphilias. 44 In fact, hostility often becomes the key parameter that differentiates the group of sexual offenders from nonsexual offenders.…”
Section: Original Articlesupporting
confidence: 75%
“…First, substantial evidence from meta-analyses and literature reviews indicates that childhood abuse and neglect increased significantly the risk of developing (in general) negative emotion dysregulation (Dvir et al ., 2014; Infurna et al ., 2016). Although this seems to be particularly the case for anxiety/depressive mood dysregulation (Dvir et al ., 2014; Infurna et al ., 2016), childhood abuse also appears to impact significantly the course of anger dysregulation (Kolla et al ., 2013; Liu et al ., 2013; Gardner et al ., 2014; Iverson et al ., 2014; Ramirez et al ., 2015). Second, several findings suggest that impulsivity is a core feature of negative emotion psychopathologies (Links et al ., 1999; Sebastian et al ., 2013; Berg et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, childhood sexual abuse, emotional neglect, and observing domestic violence during childhood were associated with greater arrests for sex crimes. Additional associations have been reported linking ACEs to increased violence and weapons use among sex offenders (Ramirez et al, 2015), to increased maladaptive cognitive schemas (Chakhssi et al, 2013), and to diverse forms of serious sexual offending (Cale et al, 2014;Connolly and Woollons, 2008;DeLisi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%